Rootstock, scion, and microbiome contributions to cadmium mitigation in five Indonesian cocoa cultivars. - Schmidt, Jennifer Elise; Dorman, Mikael; Ward, Andrew; Firl, Alana (Indonesian Coffee and Cocoa Research Institute, 2023)
Reducing levels of heavy metals such as cadmium (Cd) in cacao beans has become an important priority for cacao production in Indonesia. Current mitigation strategies revolve around breeding and the use of soil ameliorants, and in the future, the soil microbiome may also have the potential to reduce Cd bioavailability and uptake by cacao trees. However, there remains a need for locally specific recommendations for low-Cd-accumulating cacao cultivars and knowledge of native beneficial bacteria and fungi. In a greenhouse study using field soil supplemented with Cd, five cacao clones (MCC02, M01, S1, S2, and ICCRI 9) were grafted in a fully factorial design to the same hybrid half sibling rootstocks, plant uptake was measured before and after the addition of cadmium nitrate, and rhizosphere microbial communities were characterized. Rootstock, scion, and graft combinations all significantly affected plant Cd levels, but the ranking of clones differed between low and high Cd soils. Twenty-six bacterial taxa and one fungal taxon were associated with Cd uptake. These results highlight the continued importance of breeding as a cadmium mitigation strategy and support the potential for the soil microbiome to contribute to reducing cadmium uptake in cacao.